Desarrollo de una propuesta de proceso para la producción de biodiésel partiendo de residuos grasos de pollo (2020)
This paper presents an alternative for the biofuels sector in Colombia, through the theoretical study of the production of biodiesel from chicken fatty waste, since this biofuel, in addition to complying with the quality parameters according to the corresponding regulations (standard ASTM D6751), is obtained from a significant residue generated in the processing plants, whose value can reach 6.13 tons per month. Based on a bibliographic review of different authors who obtained biodiesel from the same raw material (chicken fat), the operating conditions and unit processes were compiled such as: oil extraction, oil pretreatment by esterification, due to the high FFA (free fatty acids) content of chicken oil, followed by transesterification and purification of biodiesel. In this way, a process was proposed to produce this biofuel on a pilot scale, starting from 400 kilograms of chicken fatty waste, per day. A biodiesel yield was obtained with respect to the raw material and the extracted oil of 61.48% and 87.2%, respectively. The production costs on a pilot scale to obtain 344,030 gallons per year of this biofuel, processing 400 kilograms of fatty chicken waste per day, were $ 863'415,000, taking into account the fixed and variable costs of the process. This work represents the conceptual basis to continue with the research and carry out a study on the feasibility on an industrial scale of the production of biodiesel from chicken fatty waste.